Impact of physical therapy on muscle strength in patients with degenerative hip changes (Journal of Health Sciences, 2018)
Introduction: An increasing number of people suffer from degenerative diseases of the hip joints. Many studies report the long-term outcomes of invasive therapy in the treatment of coxarthrosis. However, results of prolonged conservative treatment are scarce. The purpose of this study was to evaluate the effects of prolonged conservative physical therapy on functional recovery of degenerative hip changes.Methods: We retrospectively analyzed 47 patients diagnosed with coxarthrosis according to the American College of Rheumatology criteria. Data on sex and age, duration of physical therapy, the type of physical therapy, the values of manual muscle test (MMT) at admission and discharge, were taken from the medical records of the patients.Results: There were 76.6% female and 23.4% male patients. Half of the patients were 70 or more years old. Majority of patients were treated by kinesiotherapy (74.5%) and had significantly different (p < 0.05) values of MMT at admission and discharge. Duration of treatment was 10-20 days for 23.4% of patients, while 29.8% received treatment for 31-40 days.Conclusion: According to our results, MMT significantly improved at the end of the treatment. Thus, physical therapy had a positive effect on the recovery of muscle strength in patients with coxarthrosis.